2020
DOI: 10.5606/ehc.2020.74300
|View full text |Cite
|
Sign up to set email alerts
|

Stepped osteotomy of femoral head autograft for acetabular reconstruction in total hip arthroplasty for dysplasia of the hip: 3 to 12 years’ results

Abstract: This study aims to describe a stepped osteotomy technique applied to the femoral head autograft to keep the graft volume at a sufficient level, provide primary stability, and direct cancellous-cancellous bone contact. Patients and methods: In this retrospective study, 24 hips of 20 patients (5 males, 15 females; mean age 53 years; range, 43 to 68 years) with dysplasia of the hip (DDH) who underwent total hip arthroplasty with femoral head stepped osteotomy technique were evaluated between April 2003 and June 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…This study demonstrates that reconstructing the true acetabulum in dysplastic hips (Crowe I-III) with FHA can be successfully accomplished via a DAA with significant improvements in clinical and radiographic outcomes. Although satisfactory clinical and radiographic outcomes have been demonstrated using similar techniques and indications through alternative surgical approaches [ [3] , [4] , [5] , [18] , [19] , [20] , [21] , [22] ], potential advantages of the DAA include (1) direct exposure of the anterolateral acetabular defect, that is, typical of dysplastic hips [ 28 ]; (2) the use of intraoperative fluoroscopy, which facilitates graft placement and fixation, component positioning, and restoration of LLDs [ [31] , [32] , [33] ]; (3) an expediated functional recovery with prior studies demonstrating improvements in early gait, reduced hospital LOS, minimal activity restrictions, a low dislocation rate, and reduced postoperative pain [ 20 , [24] , [25] , [26] ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study demonstrates that reconstructing the true acetabulum in dysplastic hips (Crowe I-III) with FHA can be successfully accomplished via a DAA with significant improvements in clinical and radiographic outcomes. Although satisfactory clinical and radiographic outcomes have been demonstrated using similar techniques and indications through alternative surgical approaches [ [3] , [4] , [5] , [18] , [19] , [20] , [21] , [22] ], potential advantages of the DAA include (1) direct exposure of the anterolateral acetabular defect, that is, typical of dysplastic hips [ 28 ]; (2) the use of intraoperative fluoroscopy, which facilitates graft placement and fixation, component positioning, and restoration of LLDs [ [31] , [32] , [33] ]; (3) an expediated functional recovery with prior studies demonstrating improvements in early gait, reduced hospital LOS, minimal activity restrictions, a low dislocation rate, and reduced postoperative pain [ 20 , [24] , [25] , [26] ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite conflicting historical concerns of long-term graft resorption [ 15 ], recent literature has been largely positive for FHA [ [3] , [4] , [5] , [18] , [19] , [20] , [21] , [22] ]. In the present series, there was radiographic evidence of graft incorporation in all patients at a mean time of 6.5 months, which is comparable to alternative surgical approaches [ 3 , 4 ], with no evidence of component loosening or graft collapse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to improve the initial cup stability, an acetabular cup should be used to ensure a coverage of at least 70% 6 ; if this is not achieved, other methods should then be considered, including structural autograft with bulk femoral head, 28 controlled fracture of the medial wall, 29 medial protrusion technique, 30 and use of extra‐small cups 31 . The structural autograft technique may result in bone graft nonunion, collapse, and absorption, however some studies had reported this technique provided encouraging long‐term clinical results 32,33 . For this study, the structural autograft technique was applied in one patient, the medial protrusion technique was used in some patients, whereas others underwent routine surgery without using the above methods; additionally, all cups were not less than 44 mm in size.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Arthroplasty articles submitted to our journal from European countries are only inpatient reports. [4][5][6][7][8][9] However, outpatient arthroplasty has gained popularity over time, as the fast-track concept has evolved with perioperative treatment with rapid recovery protocols, leading to enhanced recovery after surgery and reduced length of hospital stay and cost.…”
mentioning
confidence: 99%